Mapping of sub-watersheds from digital elevation model: A morphological approach - CHOCKALINGAM, L. (2003)
This short. note presents an application of an algorithm to extract two singular networks of topological interest, such as channel and ridge connectivity networks, from a contour based Digital Elevation Model (DEM) of a region with hilly terrain. From these two extracted networks, a sub-watershed map of this region has been automatically generated. This study facilitates in understanding the watershed morphological processes in a firm quantitative manner in discrete space.